Technological challenges in the development of silica-titania platform for integrated optics - Kilicaslan, Ezgi; Butt, Muhammad Ali; Kazmierczak, Andrzej; Piramidowicz, Ryszard (Photonics Letters of Poland, 2023)
This short report discusses the technological challenges of silica-titania (SiO2:TiO2) thin film deposited via a simple, cost-effective sol-gel process and dip-coating method. Sol-gel is a versatile method for producing materials by using a solution (sol) that undergoes a gelation process to form a solid network (gel). This process involves hydrolysis and condensation reactions of precursor molecules. Although the sol-gel application is simple and economical, it has some limitations. The aging of sol-gel materials causes a change in the properties and structure of a sol-gel system over time, causing a deterioration in the final properties of the waveguide thin films. Nanoimprint lithography is a cost-effective patterning technique that is only effective when fresh sol is used; otherwise, it leads to the formation of defective waveguide structures. Full Text: PDF References M. Ebelmen, Annl. Chim. Phys. 1846(16), 129 (1846). CrossRef H.C. Vasconcelos, Waveguide technologies in Photonics and Microwave Engineering (IntechOpen, 2020). CrossRef X. Orignac, H.C. Vasconcelos, R.M. Almeida, "Structural study of SiO2 TiO2 sol—gel films by X-ray absorption and photoemission spectroscopies", J. Non-Crystalline Solids 217, 155 (1997). CrossRef X. Orignac, H.C. Vasconcelos, X.M. Du, R.M. Almeida, "Influence of Solvent Concentration on the Microstructure of SiO2-TiO2 Sol-Gel Films", J. sol-gel Scien. Technol. 8, 243 (1997). CrossRef P. Karasiński, J. Jaglarz, J. Mazur, "Low loss silica-titania waveguide films", Photonics Lett. Pol. 2, 37 (2010). CrossRef A.I.G. Varela et al., Recent Applications in Sol-Gel Synthesis (InTech 2017) DirectLink M.A. Butt, "Thin-Film Coating Methods: A Successful Marriage of High-Quality and Cost-Effectiveness—A Brief Exploration", Coatings 12, 1115 (2022). CrossRef M.A. Butt, C. Tyszkiewicz, P. Karasiński, M. Zięba, A. Kaźmierczak, M. Zdończyk, L. Duda, M. Guzik, J. Olszewski, T. Martynkien, A. Bachmatiuk, R. Piramidowicz, "Optical Thin Films Fabrication Techniques—Towards a Low-Cost Solution for the Integrated Photonic Platform: A Review of the Current Status", Materials 29, 4591 (2022). CrossRef M.A. Butt, C. Tyszkiewicz, K. Wojtasik, P. Karasinski, A. Kazmierczak, R. Piramidowicz, "Subwavelength Grating Waveguide Structures Proposed on the Low-Cost Silica–Titania Platform for Optical Filtering and Refractive Index Sensing Applications", Int. J. Mol. Sci. 23, 6614 (2022). CrossRef L. Guo, "Nanoimprint Lithography: Methods and Material Requirements", Adv. Mater. 19, 495 (2007). CrossRef V. Prajzler, V. Chlupaty, P. Kulha, M. Neruda, S. Kopp, M. Muhlberger, "Optical Polymer Waveguides Fabricated by Roll-to-Plate Nanoimprinting Technique", Nanomaterials 11, 724 (2021). CrossRef A. Cherala, P.N. Pandya, K.M. Liechti, S.V. Sreenivasan, "Extending the resolution limits of nanoshape imprint lithography using molecular dynamics of polymer crosslinking", Microsyst. Nanoeng. 7, 13 (2021). CrossRef K. Wojtasik, M. Zieba, C. Tyszkiewicz, W. Pakiela, G. Zak, O. Jeremiasz, E. Gondek, K. Drabczyk, P. Karasinski, "Zinc Oxide Films Fabricated via Sol-Gel Method and Dip-Coating Technique–Effect of Sol Aging on Optical Properties, Morphology and Photocatalytic Activity", Materials 16, 1898 (2023). CrossRef A. Kaźmierczak, M.A. Butt, M. Zięba, C. Tyszkiewicz, P. Karasiński, R. Piramidowicz, "Towards the most convenient configuration of integrated photonic sensor for implementation in SiO2:TiO2 sol-gel derived waveguide film technology", Proc. SPIE 12139, Optical Sensing and Detection VII; 1213908 (2022). CrossRef K. Racka-Szmidt, B. Stonio, J. Żelazko, M. Filipiak, M. Sochacki, "A Review: Inductively Coupled Plasma Reactive Ion Etching of Silicon Carbide", Materials 24, 123 (2021). CrossRef M.A. Butt et al."Development of a low-cost silica-titania optical platform for integrated photonics applications", Opt. Expr. 30, 23678 (2022). CrossRef S. Barcelo, Z. Li, "Nanoimprint lithography for nanodevice fabrication", Nano Converg. 3, 21 (2016). CrossRef J-H. Shin, S-H. Lee, K-J. Byeon, K-S. Han, H. Lee, K. Tsunozaki, "Fabrication of flexible UV nanoimprint mold with fluorinated polymer-coated PET film", Nanoscale Res. Lett. 6, 458 (2011). CrossRef U. Tahir, Y.B. Shim, M.A. Kamran, D-I. Kim, M. Y. Jeong, "Nanofabrication Techniques: Challenges and Future Prospects", J. Nanosc. Nanotechnol. 21, 4981 (2021). CrossRef M.A. Butt, M. Shahbaz, L. Kozłowski, A. Kaźmierczak, R. Piramidowicz, "A Concise Review of the Progress in Photonic Sensing Devices", Photonics 10, 208 (2023). CrossRef M.A. Butt et al. "HYPHa project: a low-cost alternative for integrated photonics", Photonics Lett. Pol. 14, 25 (2022). CrossRef